WELFARE OF THE FISHERMEN COMMUNITY OF SOUTH TABULO VILLAGE, MANANGGU DISTRICT, BOALEMO REGENCY, GORONTALO - Zhulmaydin Chairil Fachrussyah; Fikriyan Mahmud; Nuralim Pasisingi (Jurnal Perikanan Unram, 2024)
South Tabulo Village is one of the coastal areas of Gorontalo where most of the community are fishermen. This research aimed to determine the level of welfare of fishermen in South Tabulo Village, Mananggu District, Boalemo Regency, using Fisherman Exchange Rates (NTN) and modified Central Statistics Agency (BPS) indicators. The research was carried out from July to September 2022. Structured interviews were conducted with 46 respondents. The data obtained was analyzed quantitatively descriptively using two approaches, namely NTN and modification of welfare indicators according to BPS. The results of the research show that based on the NTN analysis, the fishing community in South Tabulo Village, Mananggu District, Boalemo Regency, has a fairly good level of welfare and the potential to save for non-primary needs with a score of 132. Based on the modified BPS welfare indicator, the fishing community is at a medium welfare level with a score of 2.6.